Six month impact of false positives in an Australian infant hearing screening programme. Issue 1 (1st January 2003) - Poulakis, Z; Barker, M; Wake, M
Abstract : Aims: To assess short and longer term parent reported impacts of false positive referrals in the Victorian Infant Hearing Screening Program (VIHSP). Methods: Mailed retrospective case-control survey of infants consecutively referred to VIHSP between December 1998 and April 1999 for whom audiology did not confirm permanent hearing loss, comprising 137 infants screened with a neonatal risk factor questionnaire and 148 older infants screened with two consecutive behavioural (distraction) tests. The two control groups comprised non-referred screened infants matched by domicile, age, and gender. Main outcome measures were parent reported emotions experienced before and after child's audiology test, parent estimated impact of hearing loss, the Child Vulnerability Scale, audiology assessment satisfaction questionnaire, and questions relating to their child's hearing and language development. Results: Final sample: at risk cases (AR) 108 (79% response), at risk controls 64 (51%); distraction test cases (DT) 103 (70%), distraction test controls 53 (41%). Parents across all groups believed that hearing loss would have major effects on a child's language (91–96%), schooling (81–91%), and employment opportunities (67–75%). Before audiology, 71% (AR) and 72% (DT) of case parents were anxious/worried, falling to 4% and 15% afterwards. After the test 82% (AR) and 79% (DT) reported relief, but 19% and 18% continued to feel worried. Ongoing concerns about hearing, language, development, and general health were comparable for AR cases compared to controls, and for DT cases compared to controls. Conclusions: Hearing screening tests are generally well received. Parents are realistic about the impact of childhood hearing loss and report a range of negative emotions when a false positive hearing screen requires referral. Although most are reassured by a normal test, a substantial number report continuing concern.